2018
DOI: 10.1038/sdata.2018.183
|View full text |Cite
|
Sign up to set email alerts
|

Chemotactic responses of growing neurites to precisely controlled gradients of nerve growth factor

Abstract: Chemotaxis plays a key role in many biological systems. In particular in the context of the developing nervous system, growing neurites can respond in vitro to shallow gradients of chemotropic molecules such as nerve growth factor (NGF). However, in such studies the gradient parameters are often not well controlled. Here we present a dataset of ~3500 images of early postnatal rat dorsal root ganglion (DRG) explants growing in 40 different precisely controlled combinations of absolute concentration and gradient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…Simulations of this model recapitulate experimentally observed features of cytoskeletal re-organization in response to guidance cues, including MT invasion of the growth cone periphery in the direction of the turn, and attenuation of retrograde flow accompanied by additional MT accumulation at sites of increased substrate adhesion. The simulated degree of turning is directly correlated to the steepness of an external signal gradient, in agreement with in-vitro observations of axonal alignment with chemotactic gradients (Bicknell et al, 2018 ). A prediction of this model is that growth cone turning is most effective for an intermediate level of sensitivity of the actin-adhesion “clutch” to the presence of MTs at the leading edge (characterized by our model parameter β): If adhesion increases in response to MTs, and attenuation of retrograde flow further promotes the local accumulation of MTs, this allows the growth cone to amplify its mechanical response to an external gradient.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Simulations of this model recapitulate experimentally observed features of cytoskeletal re-organization in response to guidance cues, including MT invasion of the growth cone periphery in the direction of the turn, and attenuation of retrograde flow accompanied by additional MT accumulation at sites of increased substrate adhesion. The simulated degree of turning is directly correlated to the steepness of an external signal gradient, in agreement with in-vitro observations of axonal alignment with chemotactic gradients (Bicknell et al, 2018 ). A prediction of this model is that growth cone turning is most effective for an intermediate level of sensitivity of the actin-adhesion “clutch” to the presence of MTs at the leading edge (characterized by our model parameter β): If adhesion increases in response to MTs, and attenuation of retrograde flow further promotes the local accumulation of MTs, this allows the growth cone to amplify its mechanical response to an external gradient.…”
Section: Discussionsupporting
confidence: 86%
“…Several lines of experimental investigation over the last several decades have demonstrated that axons are sensitive to external gradients of molecular guidance cues (Rosoff et al, 2004 ; Vitriol and Zheng, 2012 ; Goodhill, 2016 ). In-vitro assays have characterized the alignment of axonal outgrowth along gradients of guidance cue molecules (Bicknell et al, 2018 ), and axons in vitro can respond to even shallow gradients of guidance cues such as nerve growth factor (Bicknell et al, 2018 ). Patterns of molecular guidance cue gradients are present in the developing nervous system (Kennedy et al, 2006 ; Sloan et al, 2015 ), and genetic manipulation of guidance cue gradients in vivo is associated with axonal miswiring (Chédotal and Richards, 2010 ; Kang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…(2011) proposed a Bayesian model for how a gradient sensing device such as a growth cone could optimally determine gradient direction given stochastic fluctuations in receptor binding. The predicted chemotactic sensitivity curves closely matched the results of a large-scale experimental characterization of neurite sensitivity to nerve growth factor as gradient steepness and concentration were varied ( Mortimer et al., 2009 ) (the data from this study are now publicly available, Bicknell et al., 2018b ) ( Figures 4 F and 4G). This predicted sensitivity was then used to understand the results of a different experimental situation in Catig et al.…”
Section: Introductionsupporting
confidence: 70%
“…These factors are expressed endogenously by Schwann glial cells and other cell types in response to the neural injury, but this expression is often insufficient to sustain full regeneration and reinnervation [2]. In regenerative medicine, it is often desirable to not only enhance the neural regeneration in general, but to specifically direct the growing neurites towards a desired target [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Chick and mammalian DRGs have been extensively used as a convenient model to study the effect of different extrinsic treatments on neurite outgrowth, as they can be easily manipulated and easily subjected to quantification, provide consistent and reproducible results, retain the relevant tissue structure allowing proper interactions between neurons and glia and thus generally show better cell viability in vitro than pure cultures of dissociated neurons [1,3,22,23].…”
Section: Introductionmentioning
confidence: 99%